Educational Concepts from Mohammad Natsir’s Perspective and Its Relevance to Education in Indonesia - Ismail Marzuki Hasibuan; Nur Widad Mazaya; Mulia Sari (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
Long before independence, Islamic education and its existence as one of the components of national development, especially in Indonesia, played an important role in the history of this country. However, the dualism of education represented by traditional groups and Western intellectual groups made the face of education in Indonesia very dichotomous, differential and disharmonious, in addition to the education organized by the colonizers at that time did not teach religious learning at all. For this reason, Mohammad Natsir was present and appeared to carry the concept of integral, harmonious and universal education. This study aims to analyze and provide a comprehensive overview of Natsir's concept of education and its relevance to education in Indonesia. This research uses a literature review with an analytical descriptive approach. The results of this study show that Natsir's concept of education has relevance to the education system in Indonesia. This can be seen in how general subjects are taught and integrated into the pesantren curriculum, and religious subjects are integrated into the general education curriculum. Although in practice not all educational institutions in Indonesia have implemented this.